2016
DOI: 10.1128/iai.00750-16
|View full text |Cite
|
Sign up to set email alerts
|

Type II Secretion Is Necessary for Optimal Association of the Legionella-Containing Vacuole with Macrophage Rab1B but Enhances Intracellular Replication Mainly by Rab1B-Independent Mechanisms

Abstract: Previously, we documented that type II secretion (T2S) promotes intracellular infection of macrophages by Legionella pneumophila. In the present study, we identified infection events that are modulated by T2S by comparing the behaviors of wild-type and T2S mutant bacteria in murine bone marrow-derived macrophages and human U937 cells. Although the two strains behaved similarly for entry into the host cells and evasion of lysosomal fusion, the mutant was impaired in the ability to initiate replication between 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 124 publications
(156 reference statements)
2
41
0
1
Order By: Relevance
“…L. pneumophila lsp mutants that lack T2S have an Ďł10-fold reduction in intracellular growth in both U937 cells, a human macrophage-like cell line, and murine macrophages obtained from A/J mice (16)(17)(18). Data from our laboratory have also shown that this reduction in CFU is not due to an entry defect or increased degradation through the phagosome-lysosome pathway but is instead due to a replication defect in LCVs at 4 to 12 h postentry (19).…”
mentioning
confidence: 48%
See 4 more Smart Citations
“…L. pneumophila lsp mutants that lack T2S have an Ďł10-fold reduction in intracellular growth in both U937 cells, a human macrophage-like cell line, and murine macrophages obtained from A/J mice (16)(17)(18). Data from our laboratory have also shown that this reduction in CFU is not due to an entry defect or increased degradation through the phagosome-lysosome pathway but is instead due to a replication defect in LCVs at 4 to 12 h postentry (19).…”
mentioning
confidence: 48%
“…The finding that the higher cytokine levels associated with mutant strains are not evident in all species of macrophages suggested that they are not an unspecific by-product of the lspF mutation. The finding that the lspF mutant does not traffic more readily to the phagolysosome than the WT further suggests that it is not subject to greater degradation (19). Nonetheless, to determine if the lspF mutant undergoes increased lysis upon infection of human macrophages, we infected U937 cells with WT and mutant bacteria expressing cell-associated green fluorescent protein (GFP) and then assayed levels of GFP released from bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations